Feasibility to develop three dimensional national digital cadastre database using remote sensing data - Mohamad, Siti Zainun (2016)
National Digital Cadastre Database (NDCDB) contains 40 million boundary marks that are based on Geocentric Datum of Malaysia (GDM 2000) for Peninsular Malaysia and Federal Territories of Malaysia. Currently, the NDCDB is a two-dimensional (2D) planimetric coordinate database without elevation information. Enhancement of the existing NDCDB is needed in order to suit the current situation and demands for real world modelling. One way to deal with this situation is to upgrade the current database to a three dimensional (3D) Cadastre Database that provide 3D information about land. The objectives of this research are: i) to investigate and to examine the feasibility of developing the 3D NDCDB; ii) to develop a new method for providing height information in cadastre survey and iii) to evaluate the accuracy of height information generated from Light Detection and Ranging (LiDAR), Interferometric Synthetic Aperture Radar (IFSAR) and cadastre survey. Development of the 3D NDCDB involves the introduction of height information into the existing cadastre boundary marks (CBMs), extracted from various data sources such as LiDAR for urban areas in Mukim Setapak, Kuala Lumpur, IFSAR for rural areas in Mukim Simpang Kiri, Batu Pahat, Johor and from field observation in cadastre survey using the trigonometric levelling technique for new CBMs at lot 48330, Bandar Johor Bahru. The trigonometric levelling technique is used to determine the elevation difference between two stations by the triangle formula. The evaluation of accuracy of height information generated from existing CBMS is based on Root Mean Square Error (RMSE) and the accuracy of new CBMs is evaluated with reference to the accumulated error from Cadastre Reference Mark to CBMs. The results showed that the accuracy of vertical RMSE of generated height information for existing CBMs is ±11cm for LiDAR and suitable to be introduced into 3D NDCDB for urban areas. For rural area, the height accuracy is ±0.7m for IFSAR. The accuracy derived for new CBMs is ±8cm and it shows that trigonometric levelling technique is suitable to produce height information into new CBMs with several improvement in field data observation practices.